Evaluation of Particulate Matter Capture and Long-Term Clogging Characteristics of Different Filter Media for Pavement Runoff Treatment - Zhengguang Wu; Yanjuan Qi; Aihong Kang; Bo Li; Xueling Xu (Advances in Materials Science and Engineering)
The removal of particulate matter (PM) by filter media during filtration process can mitigate the pavement runoff pollution effectively. However, this process also makes the filter media prone to clogging. To better understand the size ranges of PM captured by filter media and the subsequent impact on the clogging process, filtration test and clogging test were conducted on five types of filter media. The effect of layer thickness and grain size of different filter media on particle removal efficiency was evaluated, based on the results of PM removal rate and the particle size distribution. The subsequent long-term clogging characteristics of different filter media were also investigated. The results showed that filter media presented different capabilities to capture PM, which could be enhanced by less layer thickness or finer grain size. Normally, PM with the size range of over 49 μm could be captured effectively if proper layer thickness and grain size of filter media were selected. Besides, PM removal rate was not related to the clogging resistance of filter media. Though it can capture a larger amount of PM, Vesuvianite still maintained remarkable clogging resistance. The results will be beneficial to filter media selection and system design optimization for pavement runoff treatment.